A universal approach to improve electron mobility without significant enlarging phase separation in IDT-based non-fullerene acceptor organic solar cells. (November 2017) - Zhang, Lin; Lin, Baojun; Ke, Zhifan; Chen, Jianya; Li, Wanbin; Zhang, Maojie; Ma, Wei
Abstract: An in-situ solvent annealing method of solvent annealing during spin-coating (SC-SVA) was deployed to increase the electron mobility by improving the crystallinity of non-fullerene acceptor without significant enlarging the domain size. Although similar effect can be achieved by the post solvent annealing and co-solvents methods, these methods meanwhile enlarge the phase separation in the PTB7-Th:ITIC based organic solar cells. Thus, the efficiency of SC-SVA based device results in a 20% enhancement and exhibits a better photovoltaic performance than that of the post solvent annealing and co-solvents methods. The fundamental mechanism of these three methods were analyzed and discussed in detail. As the enhanced crystallinity of non-fullerene acceptor could improve charge carrier mobility, the thick-film devices with SC-SVA were fabricated and exhibit great photovoltaic performance. Moreover, this beneficial SC-SVA method was successfully employed in the other IDT-based PTB7-Th:ITIC-Th and PTB7-Th:IEIC devices as well as in the PTZ1:IDIC binary and PTZ1:IDIC:ITIC ternary devices. The high efficiencies of 10.11% and 10.30% were achieved for the binary and ternary devices with SC-SVA, respectively, showing its excellent universality and prospect. Graphical abstract: An in-situ solvent annealing method of solvent annealing during spin-coating (SC-SVA) have been deployed to increase the electron mobility by improving the crystallinity of non-fullerene acceptor without significantly enlarging the domain size, which is successfully employed in the thick-film devices and other IDT-based binary and ternary devices with the PCE up to 10%. Highlights: The SC-SVA improves electron mobility without much enlarging phase separation size. The SC-SVA method result in fewer CF solvent molecules can enter into the blend film than the post-SVA method and co-solvents method due to the rapid rotation and the existence of CB host solvent in the wet film. The SC-SVA method is successfully used in the thick-film devices because of the increased carrier mobility. Mover, the SC-SVA method is triumphantly employed in other IDT-based devices and high efficiencies up to 10% are achieved for both binary and ternary devices with SC-SVA.